Determinant Analysis of Learning Interest in Informatics Management Students at STMIK Mulia Darma - Sihombing, Monang Juanda Tua; Trianovie, Sri (Universitas Budi Darma, 2025)
This study aims to analyze the influence of intellectual intelligence, learning motivation, and learning behavior on the learning interest of students in the Information Management Study Program at STMIK Mulia Darma. Higher education institutions play a strategic role in improving the quality of human resources, particularly in shaping intellectual and professional abilities. However, various problems still exist, including low-quality educators, limited educational facilities, and weak links between education and the needs of the workforce. Intellectual intelligence without the support of positive motivation and learning behavior cannot produce an optimal learning process. Students with low motivation and learning behavior tend to show a lack of responsibility and participation in academic activities. This study uses the Structural Equation Modeling (SEM) approach with the Partial Least Squares (PLS) method to test the relationship between latent variables. The results of this study are expected to contribute to efforts to improve the quality of learning and develop student interest in learning in higher education.